Increasing International Students’ Tuition Fees: The Two Sides of the Coin - Sanchez-Serra, Daniel; Marconi, Gabriele (International Higher Education, 2018)
While higher tuition fees contribute to better funded tertiary education systems, they also put a burden on families whose children enroll in tertiary education, especially those with limited financial means. This article explores this dilemma and identifies key questions.